Emergency Critical Care Service in Emergency Medicine Ward: The Experience in North Lantau Hospital. Issue 1 (January 2017) - Wong, OF; Ko, S; Cheung, WH; Wong, WY; Ma, HM; Lit, ACH
With the increased demand of critical care, emergency physicians often provide a significant proportion of critical care for the critically ill patients apart from their primary roles in resuscitation and initial stabilisation. The dual training pathway of emergency medicine and intensive care medicine enables the Accident and Emergency Departments (AEDs) to be staffed with emergency intensivist to provide care of critically ill patients in the AEDs beyond the initial resuscitation. North Lantau Hospital is a community hospital located in central Tung Chung of Lantau Island. Transporting critically ill patients to the nearest tertiary hospital requires a significant amount of time which poses high risk to them. An "Emergency Critical Care Management" pilot program was created under these circumstances. In this pilot program, up to 2 beds in the Emergency Medicine Ward (EMW) are used for managing critically ill patients. The experience and preliminary outcomes of implementing critical care service in the EMW are shared in this article.